A Structuralist’s View of an Indian Creation Myth - Messer, Ron (Anthropologica, 2022)
Within the mythology of the North American Indians a certain supernatural being is frequently presented as the synthesis of two apparently divergent traits of character. Here, the trickster-transformer culture hero, or trickster-hero, as he is sometimes called (Ricketts 1966:327), is at one and the same time a hero and a deceiver. The trickster-hero is both courageous and cunning, ingenious and impudent. This apparent contradiction in his personality, which appears so blatantly obvious to the student of native folklore and mythology, is taken as a matter of course by the native American Indian. It will also provide the focal point for the investigation to be undertaken.